Tafsir Ahkam Fii Muamalah Konsep Akuntansi dalam Ekonomi Syariah - Nuranisya, Siti; Bisri, Hasan; Kama, Mustopa (Sharia Journal and Education Center Publishing, 2025)
This research aims to explore the concept of accounting from an Islamic economic perspective through the Tafsir Ahkam (legal interpretation) approach. The primary focus of this study is how the muamalah verses in the Qur'an, particularly Surah Al-Baqarah verse 282, lay the fundamental foundations for the principles of bookkeeping, accountability, and financial transparency. The research method employed is qualitative, using a library research approach to examine books of legal exegesis. The findings indicate that Islamic accounting is not merely a commercial calculation tool but a form of moral and religious accountability to Allah SWT and fellow human beings. The principles of justice ('adl), truthfulness (sidq), and trustworthiness (amanah) serve as the main pillars in preparing Sharia-compliant financial statements. The implications of this research emphasize that integrating Tafsir Ahkam values into modern accounting standards is crucial for maintaining the integrity of the Islamic economic ecosystem.